2021
DOI: 10.1186/s12887-021-02830-w
|View full text |Cite
|
Sign up to set email alerts
|

The full spectrum of ethical issues in pediatric genome-wide sequencing: a systematic qualitative review

Abstract: Background The use of genome-wide sequencing in pediatric medicine and research is growing exponentially. While this has many potential benefits, the normative and empirical literature has highlighted various ethical issues. There have not been, however, any systematic reviews of these issues. The aim of this systematic review is to determine systematically the spectrum of ethical issues that is raised for stakeholders in in pediatric genome-wide sequencing. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…The reasoning they offered for this was that they had had high expectations that a diagnosis, or at least a VUS, would be achieved with WES. The finding that disappointment occurs, or even increases, when persons have heightened or unrealistic expectations about the type of result they will receive, is consistent with insights of other empirical studies and points to acknowledging expectation management as part of the informed consent process (Bos & Bunnik, 2022;Donohue et al, 2021;Eichinger et al, 2023;Peter et al, 2022;Wynn et al, 2018). However, our results show that this observation should be built upon further, since parents who adopted a hopeful stance about what WES might offer them reported being ultimately more satisfied with the whole sequencing experience than the couple in our study who expected a certain outcome or answers from WES and thus reported being disappointed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The reasoning they offered for this was that they had had high expectations that a diagnosis, or at least a VUS, would be achieved with WES. The finding that disappointment occurs, or even increases, when persons have heightened or unrealistic expectations about the type of result they will receive, is consistent with insights of other empirical studies and points to acknowledging expectation management as part of the informed consent process (Bos & Bunnik, 2022;Donohue et al, 2021;Eichinger et al, 2023;Peter et al, 2022;Wynn et al, 2018). However, our results show that this observation should be built upon further, since parents who adopted a hopeful stance about what WES might offer them reported being ultimately more satisfied with the whole sequencing experience than the couple in our study who expected a certain outcome or answers from WES and thus reported being disappointed.…”
Section: Discussionsupporting
confidence: 81%
“…A simple reminder that hopes are inherently different from expectations may help protect against overly optimistic assumptions and disappointment. This finding can be added to insights generated on expectation management found elsewhere that have stressed the need to mitigate against false hopes and unrealistic expectations through various strategies, such as encouraging parents to take some extra time to reflect on their choices in more detail before actually obtaining written consent for sequencing (Bos & Bunnik, 2022;Eichinger et al, 2023;Gore et al, 2019;Wynn et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…Notably, in Turkey, the formal establishment of genetic counseling as a profession is yet to be realized, resulting in clinical geneticists assuming the responsibility of guiding patients through both preand post-test phases. This task, which can be particularly challenging, has been referred to as a "nightmare" in other countries (Eichinger et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Testing children for cancer predisposition is a topic of ongoing ethical debate [ 5 ]. This debate encompasses various issues, including what information should be provided during the consent process, what appropriate timing of consent would be, how children should be involved in decision-making, and whether re-consent is desirable when children reach the age of majority.…”
Section: Introductionmentioning
confidence: 99%